2024
DOI: 10.3847/1538-4357/ad13f1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Electron Secondary Reconnection in Magnetic Reconnection Front

C. M. Liu,
J. B. Cao,
X. N. Xing
et al.

Abstract: Magnetic reconnection, a fundamental plasma process transforming magnetic field energy into particle energy, is ubiquitous in space and responsible for many explosive phenomena, such as solar flares and gamma-ray bursts. Recent numerical theories have predicted that reconnection fronts far from the primary reconnection region can host secondary reconnection in three-dimensional scenarios, different from the conventional two-dimensional diagram where only one X-line stands to sustain reconnection. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Observations and simulations have recently revealed that the DFs typically host strong energy conversion processes, manifested in the form of particle acceleration and heating (e.g., Birn et al, 2013;Gabrielse et al, 2016;Lu et al, 2016;Runov et al, 2015;Xing et al, 2023;Zhou et al, 2013), wave-particle or wave-wave interactions (e.g., Chen et al, 2022;Hwang et al, 2014;Liu et al, 2021;Zhou et al, 2009) These studies have suggested that during the DF-driven energy conversion, particles propagating along with the DFs usually gain energy from the electromagnetic fields (dominated by energy loads), with the released electromagnetic energy primarily transferred to ions (e.g., Huang et al, 2015;Khotyaintsev et al, 2017;Lapenta et al, 2014; C. M. Liu, Cao, & Pollock, 2022a;Sitnov et al, 2009;Wang et al, 2020;Yao et al, 2017;Zhong et al, 2019), whereas electron energy gain can also dominate in some cases (Liu et al, 2018). It has been documented that the DF-driven energy conversion is not only closely related to local particle dynamics, but also affects the global energy transfer processes in the magnetotail (e.g., Angelopoulos et al, 2013;Hamrin et al, 2011Hamrin et al, , 2013Liu, Vaivads, et al, 2022, 2024.…”
Section: Introductionmentioning
confidence: 99%
“…Observations and simulations have recently revealed that the DFs typically host strong energy conversion processes, manifested in the form of particle acceleration and heating (e.g., Birn et al, 2013;Gabrielse et al, 2016;Lu et al, 2016;Runov et al, 2015;Xing et al, 2023;Zhou et al, 2013), wave-particle or wave-wave interactions (e.g., Chen et al, 2022;Hwang et al, 2014;Liu et al, 2021;Zhou et al, 2009) These studies have suggested that during the DF-driven energy conversion, particles propagating along with the DFs usually gain energy from the electromagnetic fields (dominated by energy loads), with the released electromagnetic energy primarily transferred to ions (e.g., Huang et al, 2015;Khotyaintsev et al, 2017;Lapenta et al, 2014; C. M. Liu, Cao, & Pollock, 2022a;Sitnov et al, 2009;Wang et al, 2020;Yao et al, 2017;Zhong et al, 2019), whereas electron energy gain can also dominate in some cases (Liu et al, 2018). It has been documented that the DF-driven energy conversion is not only closely related to local particle dynamics, but also affects the global energy transfer processes in the magnetotail (e.g., Angelopoulos et al, 2013;Hamrin et al, 2011Hamrin et al, , 2013Liu, Vaivads, et al, 2022, 2024.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic reconnection (Biskamp 1986)-a topology-reorganization process through which magnetic field lines get cut and reconnected-has been well documented, by spacecraft observations, laboratory experiments, and numerical simulations, as one of the most powerful engines in transforming electromagnetic energy into particles' kinetic and thermal energies in space and and laboratory plasmas (e.g., Yamada et al 2010). Reconnection has been suggested to play a vital role in fusion disruption on the ground, substorms in the planetary magnetosphere, flares on the Sun and near the black holes, as well as gamma-ray bursts in deep space (e.g., Paschmann et al 1979;Angelopoulos et al 2020;Antolin et al 2020;Chibueze et al 2021;Yan et al 2022;Liu et al 2024). Owing to its ubiquity and importance, reconnection has been extensively investigated, both experimentally and theoretically, for more than eight decades (e.g., Pritchett 2001;Cao et al 2013;Lu et al 2020;Pontin & Priest 2022;Zhou et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a localized structure, the DFs assume a crucial role in the global-scale energy conversion as they propagate toward the Earth (e.g., Angelopoulos et al, 2013;C. M. Liu, Cao, Wang, & Xing, 2022;C. M. Liu et al, 2024).…”
Section: Introductionmentioning
confidence: 99%